Combination Microfinance and HIV Risk Reduction Among Women Engaged in Sex Work. (February 2023) - Witte, Susan S.; Yang, Lyla Sunyoung; McCrimmon, Tara; Aira, Toivgoo; Batsukh, Altantsetseg; Terlikbayeva, Assel; Primbetova, Sholpan; Mergenova, Gaukhar; Cordisco Tsai, Laura; Carlson, Cady; Vélez-Grau, Carolina; Ssewamala, Fred; et al.
The purpose of this paper is to summarize 15 years of intervention science in combination HIV prevention and microfinance among women engaged in sex work (WESW) in Central Asia, identifying gaps in our understanding and recommendations for future studies. We begin by describing the emergence of HIV/STI risk among WESW in the Central Asia region, specifically Mongolia and Kazakhstan, and bridge to the formative stages of our methodology as well as completed prevention intervention studies. We describe the development of combining HIV prevention with asset-based microfinance interventions, lessons learned, and contributions these studies make to HIV prevention, intervention science, and practice. We end by recommending next steps to move prevention science forward in this area and among this key population, which continues to be underserved in HIV prevention science worldwide.